Validasi Pulse oximeter dalam Penentuan Kadar Oksigen dalam Darah - Umi Salamah; Asna Nur Izziyah; Arifan Arif Raharjo (Jurnal Teori dan Aplikasi Fisika, 2020)
The level of oxygen saturation in the blood is important to know the health condition of the body. If the human body lacks or excess oxygen, it will cause illness and other bodily system work disorders. One of the tools to detect the oxygen saturation level is the Pulse oximeter. Previous research has successfully designed a Pulse oximeter based on Arduino. The pulse oximeter produces a photoplethysmograph (PPG) signal that corresponds to the standard PPG signals in 20 test samples. PPG signals can be processed to provide information on oxygen saturation (SpO2) levels in the blood. In this research, validation of the Pulse oximeter is compared with a commercial pulse oximeter, the digital oximeter JZK-301. The results obtained from this validation are the smallest deviation errors are 4.83% while the largest errata is 22.51%. The greatest accuracy of 95.17%, of respondents number 16 and the smallest accuracy is 77, 49%, that is the number of respondents 12. The average deviation of 20 data is 12.82% with the resulting accuracy is 87, 18%. This indicates that the self-designed pulse oximeter has good efficiency and can be developed further